Intuitive Thinking and its Relationship to Mathematical Proficiency among Female Students in the Second Intermediate Grade - Majeed, Zinah Mezaal (NIU Journal of Social Sciences; Vol 12 No 2 (2026): NIU Journal of Social Sciences, Vol. 12 No. 2, June 2026DO - 10.58709/niujss.v12i2.2616, 2026)
This study's overarching goal is to shed light on the association between second-intermediate-grade female students' levels of intuitive thinking and mathematical aptitude. Stratified random sampling was used to select 150 female students in the second intermediate grade from two schools affiliated with the Baghdad Directorate of Education, Al-Rusafa II: Itr Al-Ward and Al-Kawakib. Fifty students from each school made up the research sample. The research methodology followed a descriptive correlational approach. After ensuring their validity and reliability, the researcher administered a math competency exam and an intuitive thinking measure to the sample. The findings demonstrated that second-grade intermediate pupils outperform the theoretical mean for both intuitive thinking (mean of 72.84) and mathematical competency (mean of 30.38). Intuitive thinking and mathematical proficiency were found to be positively and statistically significantly correlated with one another (Pearson correlation coefficient = 0.64), although there were no discernible differences in either variable between the two schools' students. Based on these findings, the researcher emphasized the need of exposing middle school children to a variety of mathematical settings in order to foster intuitive thinking rather than restricting mathematics instruction to rote memory and rule application. Keywords: intuitive thinking, mathematical proficiency, second-year intermediate stage, descriptive correlational approach.